THE MUSICALITY OF STYLE – LÁSZLÓFFY ZSOLT’S ESSAYS ON MUSIC (LÁSZLÓFFY ZSOLT: A STÍLUS ZENEISÉGE. PARTIUM KIADÓ, NAGYVÁRAD, 2014) - FODOR, Attila (Studia Universitatis Babes-Bolyai Musica, 2015)
As a representative of the Transylvanian composers’ younger generation, Zsolt Lászlóffy marks out not only by his exciting works and intense performing activities, but also through his writings. Behind his versatile output lays a keen commitment toward the Hungarian culture of his native land, that of protecting and promoting - as a musician - our cultural heritage. Through this new opus the readers are invited to discover, along with the author, another field of his musical adventures, sounding experiences and exciting wanderings in style and aesthetics.